Motor associations of iron accumulation in deep grey matter nuclei in Parkinson's disease: a cross‐sectional study of iron‐related magnetic resonance imaging susceptibility - Antonio Martín‐Bastida; Nicholas P Lao–Kaim; Clare Loane; Marios Politis; Andreas–Antonios Roussakis; Natalie Valle‐Guzman; Zinovia Kefalopoulou; Gesine Paul-Visse; Håkan Widner; Yue Xing; S. Schwarz; Dorothee P. Auer; et al. (2016)
To determine whether iron deposition in deep brain nuclei assessed using high-pass filtered phase imaging plays a role in motor disease severity in Parkinson's disease (PD).Seventy patients with mild to moderate PD and 20 age- and gender-matched healthy volunteers (HVs) underwent susceptibility-weighted imaging on a 3 T magnetic resonance imaging scanner. Phase shifts (radians) in deep brain nuclei were derived from high-pass filtered phase images and compared between groups. Analysis of clinical laterality and correlations with motor severity (Unified Parkinson's Disease Rating Scale, Part III, UPDRS-III) were performed. Phase shifts (in radians) were compared between HVs and three PD subgroups divided according to UPDRS-III scores using analysis of covariance, adjusting for age and regional area.Parkinson's disease patients had significantly (P < 0.001) higher radians than HVs bilaterally in the putamen, globus pallidus and substantia nigra (SN). The SN contralateral to the most affected side showed higher radians (P < 0.001) compared to the less affected side. SN radians positively correlated with UPDRS-III and bradykinesia-rigidity subscores, but not with tremor subscores. ancova followed by post hoc Bonferroni-adjusted pairwise comparisons revealed that SN radians were significantly greater in the PD subgroup with higher UPDRS-III scores compared to both lowest UPDRS-III PD and HV groups (P < 0.001).Increased nigral iron accumulation in PD appears to be stratified according to disease motor severity and correlates with symptoms related to dopaminergic neurodegeneration. This semi-quantitative in vivo iron assessment could prove useful for objectively monitoring PD progression, especially in clinical trials concerning iron chelation therapies.